2020
DOI: 10.1192/bjo.2020.146
|View full text |Cite
|
Sign up to set email alerts
|

Ethno-cultural disparities in mental health during the COVID-19 pandemic: a cross-sectional study on the impact of exposure to the virus and COVID-19-related discrimination and stigma on mental health across ethno-cultural groups in Quebec (Canada)

Abstract: Background Although social and structural inequalities associated with COVID-19 have been documented since the start of the pandemic, few studies have explored the association between pandemic-specific risk factors and the mental health of minority populations. Aims We investigated the association of exposure to the virus, COVID-19-related discrimination and stigma with mental health during the COVID-19 pandemic, in a culturally diverse sample of adults in Quebec (Canada). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 35 publications
(40 reference statements)
6
78
1
1
Order By: Relevance
“…Results are consistent with a recent Canadian study that found that 22% of South Asian participants consider that COVID-19 had impacted their mental health “a great deal” compared to 11% of East Asians (e.g. Chinese) [ 28 ]. Differences in depression symptoms during the COVID-19 pandemic among South Asians and Chinese may be attributed to a combination of factors.…”
Section: Discussionsupporting
confidence: 91%
“…Results are consistent with a recent Canadian study that found that 22% of South Asian participants consider that COVID-19 had impacted their mental health “a great deal” compared to 11% of East Asians (e.g. Chinese) [ 28 ]. Differences in depression symptoms during the COVID-19 pandemic among South Asians and Chinese may be attributed to a combination of factors.…”
Section: Discussionsupporting
confidence: 91%
“…A Canadian study found that minority groups experience greater COVID-19 related mental health issues compared to non-minority groups, including depression and anxiety [ 39 ]. In a US study, individuals with lower social resources, lower economic resources and greater exposure to stressors (losing a job, death of a family member from COVID-19, experiencing financial problems) were more susceptible to depression, with lower income respondents at 2.37 times higher risk of depression [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…At present, the only known data on COVID-19 infection and its related discrimination and stigma on mental health across ethnocultural groups in Canada found that Blacks (38.72%) had the greatest virus exposure among all ethnocultural groups. Black participants also experienced the worst mental health outcomes when exposed to COVID-19 virus and/or its related discrimination, compared with other socio-cultural groups (Miconi et al, 2021 ). Such evidence supports preliminary reports from the United States and the United Kingdom that communities of colour are disproportionately affected by COVID-19 due to the long-existing social and economic disparities they face.…”
Section: Health Inequalitiesmentioning
confidence: 99%